Impact of switching from digital mammography to tomosynthesis plus digital mammography on breast cancer screening in Alberta, Canada. (March 2022) - Pang, Jack XQ; Newsome, James; Sun, Maggie; Chiang, Bonnie; Mutti-Packer, Seema; McDonald, Sheila W; Yang, Huiming
Objectives: To compare abnormal call rates (ACR), cancer detection rates (CDR), positive predictive values (PPVs), and annual return to screen recommendations after switching from digital mammography (DM) to digital breast tomosynthesis plus DM (DBT + DM) for breast cancer screening. Setting: The Alberta Breast Cancer Screening Program collects screening data from clinics throughout the province of Alberta, Canada. Methods: This study retrospectively collected data, between 2015 and 2018, on women aged 40+ who underwent breast cancer screening at two large volume multisite radiology groups to compare metrics one year prior and one year after DBT + DM implementation. Comparisons between modalities were carried out within age groups, within breast density categories, and for initial vs. subsequent screens. Results: A total of 125, 432 DM and 128, 912 DBT + DM screening exams were performed. For women aged 50–74, the DBT + DM group had a higher ACR ( p  < 0.01) but lower annual return to screens ( p  < 0.01). CDR was higher post-DBT + DM implementation for women with scattered (6.0 per 1000 vs. 4.4 per 1000; p  = 0.001) or heterogeneously dense breasts (6.5 per 1000 vs. 4.2 per 1000; p  < 0.001). PPV was higher with DBT + DM for all age groups, with women 50–74 having a PPV of 8.3% using DBT + DM vs. 7.1% with DM ( p  = 0.009). Conclusion: All metrics improved or stayed the same after switching to DBT + DM except for ACR. However, the increase in ACR could be attributed to a trend already occurring prior to the switch. Longer term monitoring is needed to confirm these findings.